2017
DOI: 10.1021/acs.jmedchem.6b01685
|View full text |Cite
|
Sign up to set email alerts
|

Accepting the Invitation to Open Innovation in Malaria Drug Discovery: Synthesis, Biological Evaluation, and Investigation on the Structure–Activity Relationships of Benzo[b]thiophene-2-carboxamides as Antimalarial Agents

Abstract: Malaria eradication is a global health priority, but current therapies are not always suitable for providing a radical cure. Artemisinin has paved the way for the current malaria treatment, the so-called Artemisinin-based Combination Therapy (ACT). However, with the detection of resistance to ACT, innovative compounds active against multiple parasite species and at multiple life stages are needed. GlaxoSmithKline has recently disclosed the results of a phenotypic screening of an internal library, publishing a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(14 citation statements)
references
References 59 publications
0
14
0
Order By: Relevance
“…This notion may sound odd, especially if one considers the first-line antituberculosis drugs: isoniazid and pyrazinamide both have negative ClogP, whereas ClogP of ethambutol is 0.35. However, it has been deeply demonstrated that compounds with antituberculosis activity are more lipophilic than the inactive ones (Ekins et al, 2011 ), and not only in general, but also within a drug class, lipophilic derivatives are in general more active against mycobacteria than their more hydrophilic counterparts (Mao et al, 2009 ; Lilienkampf et al, 2010 , 2012 ; Pieroni et al, 2010 , 2011 , 2017 ). Below, a critical analysis of the current hot biology challenges (energy depletion, PMF, and drug transporters) and their interconnection with the lipophilicity of molecules is reported.…”
Section: State-of-the-art Of Tuberculosis Drug Discoverymentioning
confidence: 99%
“…This notion may sound odd, especially if one considers the first-line antituberculosis drugs: isoniazid and pyrazinamide both have negative ClogP, whereas ClogP of ethambutol is 0.35. However, it has been deeply demonstrated that compounds with antituberculosis activity are more lipophilic than the inactive ones (Ekins et al, 2011 ), and not only in general, but also within a drug class, lipophilic derivatives are in general more active against mycobacteria than their more hydrophilic counterparts (Mao et al, 2009 ; Lilienkampf et al, 2010 , 2012 ; Pieroni et al, 2010 , 2011 , 2017 ). Below, a critical analysis of the current hot biology challenges (energy depletion, PMF, and drug transporters) and their interconnection with the lipophilicity of molecules is reported.…”
Section: State-of-the-art Of Tuberculosis Drug Discoverymentioning
confidence: 99%
“…Benzothiophene privilege structure is among the sulfur containing fused herterocycles which are interesting in drug discovery [ 18 ]. Many lead compounds having this nucleus possess divergent pharmaceutical activities, allowing them to act as anti-inflammatory, anti-cancer, anti-diabetic, anti-oxidant, anti-microbial, anti-convulsant agents, anti-tubercular, and many more [ 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…Chalcogen-containing heterocycles are an important class of compounds that have been extensively exploited in medicinal chemistry, [1][2][3] materials science [4][5][6][7][8][9][10] and organic synthesis. [11][12][13] Among them, chalcogenophenes have presented many promising applications as new materials due to their properties as organic semiconductors, which showed potential as organic field-effect transistors (OFET), [14][15][16][17][18][19] organic light-emitting diode (OLED), [20][21][22][23][24] and organic solar cells (OSC).…”
Section: Introductionmentioning
confidence: 99%